189 Normative baseline SCAT5 scores in a population of united states olympic athletes. (3rd March 2020) - Pierpoint, Lauren; Zdziarski, Laura; Taylor, David; Moreau, William; Nabhan, Dustin
Abstract : Background: The Sport Concussion Assessment Tool 5th Edition (SCAT5) is the most recent version of the concussion evaluation tool used by clinicians to evaluate athletes with suspected concussions. Objective: To describe normative baseline SCAT5 scores among United States Olympic athletes. Design: Retrospective descriptive epidemiology. Setting: United States Olympic and Paralympic Sports Medicine Centers. Participants: Two hundred fifty-seven Olympic athletes (48.2% female, mean age ± standard deviation (SD)=22.5±4.8 years) representing 19 sport federations underwent baseline SCAT5 testing between April 2018 and July 2019. Main outcome measurements: Baseline SCAT5 scores of healthy Olympic athletes. T-tests were used to compare scores by sex. Results: Athletes reported a mean of 4.0±4.9 symptoms (median=2, IQR=0–6) with an average severity score of 7.9±12.3 (median=2, interquartile range=0–10). Most (71.8%) athletes reported never having sustained a concussion prior to testing; 17.5% reported one prior concussion (range=0–10 reported concussions). Mean scores ± SD for major components of the SCAT5: 4.8±0.53 for orientation, 20.7±4.0 for immediate memory, 3.8±1.3 for concentration, 4.0±4.2 for balance, 6.9±1.9 for delayed recall, and 12.4±3.0 for Standardized Assessment of Concussion. No sex differences were observed for concussion history or the number and severity of current symptoms. Females scored higher than males in the immediate memory (21.7 vs. 19.8, p<0.001), orientation (4.9 vs. 4.8, p=0.047), and delayed recall tasks (7.3 vs. 6.5, p=0.001). Conclusions: Normative values for baseline SCAT5 performance are presented for a population of healthy Olympic athletes. This information can be considered by clinicians interpreting SCAT5 results in athletes who do not have a known baseline score.